Waste In The Patient Discharge Process Flow Using Lean Thinking Method At Wihdatul Ummah Medical Center In 2025 - Fathannia Rizky D; AM Multazam; Nur Ulmy M; AS Batara; Sumiaty Sumiaty; Samsualam Samsualam (CV. Inara, 2025)
Background: The discharge process for inpatients is a critical component of hospital service systems, impacting operational efficiency and service quality. Inefficiencies in this phase can lead to wasted time, reduced patient satisfaction, and workflow disruptions between service units. Objective: This study aims to identify and analyze forms of waste in the discharge process of inpatients at Wihdatul Ummah Medical Center using the Lean Thinking approach. Method: This study used a qualitative descriptive design with data collection techniques through observation, document study, and in-depth interviews with 11 informants, consisting of clinic directors, doctors in charge of patients (DPJP), ward heads, nurses, administrative staff, pharmacy staff, and patients' families. Results: It was found that the discharge process did not have a well-documented and socialized written SOP. This resulted in wasted time in the form of motion waste for BPJS patients (due to physical transfers between service units) and waiting waste for non-BPJS patients (due to delays in administrative processing and medication reconciliation). The root causes include weak inter-unit coordination, manual work processes, lack of integrated information systems, and insufficient education for patients and their families. Conclusion: The study recommends the appointment of Point of Service (POS) officers, the use of discharge preparation lists, strengthening patient education, implementing visual management, and developing and implementing discharge SOPs. These efforts are expected to reduce time wastage, speed up the discharge process, and improve service quality and patient satisfaction.